UMPSA and Libya strengthen collaborative bonds for academic and research advancements - Nur Ezzati, Mohd Nasir (UMPSA, 2024)
KUALA LUMPUR, 23 April 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to foster stronger ties with Libyan academic and research institutions through a significant meeting held in Kuala Lumpur recently.